Anatomical Study of Bat’s Phalanx Bone - Nurrizki, Fani; Ristiani, Hanifah Ika; Ambarwati, Novita; Luthfi, Muhammad Jafar (Proceeding International Conference on Science and Engineering, 2020)
Bats (Pteropus sp) are nocturnal animals. Bats are mammal that are able to fly, actively foraging at night. During the day time bats spend time for sleeping. It aims to keep the wings membran from sunlight. The habitat of this bat is on large trees. The foot of the bat is adapted to hang upside down, that causing an action against phalanx that calls pressure. Each of phalanx receives a different pressure so that it affect the anatomical structure. This condition present a biomechanical. This study aims to know the effect of pressure on the phalanx. Observation are made by cleaning the phalanx skin and cutting the bones and then seen under the microscope with a magnification of 5x, measurement are taken. The result show that the pressure affect the phalanx anatomical structure that is different thicknesses in each phalanx.